2021
DOI: 10.1029/2021sw002728
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Midnight Temperature Maximum Winds on Post‐Midnight Equatorial Spread F

Abstract: The SAMI3/ESF (Sami3 is also a model of the ionosphere/equatorial spread F ) code is used to simulate the growth of equatorial plasma bubbles in the presence of a background wind field based on measured winds. The measured winds exhibit the well-known 'midnight temperature maximum' (MTM) pattern, in which an equatorward wind occurs simultaneously with a cessation in the zonal wind. The MTM is often preceded by strong equatorward winds (about 100 m/s). The circumstance where the MTM winds are symmetric across t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Similar difficulty has been noticed by Krall et al. (2021). They simulated the generation of irregularities for both high and low solar activity, but to find little differences.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar difficulty has been noticed by Krall et al. (2021). They simulated the generation of irregularities for both high and low solar activity, but to find little differences.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, γ for 2012 is only 40% lower than 2009, seemingly not enough to explains the much fewer irregularities in 2012. Similar difficulty has been noticed by Krall et al (2021). They simulated the generation of irregularities for both high and low solar activity, but to find little differences.…”
Section: 1029/2022ja031211mentioning
confidence: 99%
“…Miyoshi et al (2009) suggested that the solar terminator wave is mainly generated by the superposition of the upward propagating migrating tides, which could contribute to the generation of MTM as shown in Figure 5. The MTM winds considerably impact EPB development (Krall et al, 2021) and its longitudinal distribution. McDonald et al (2015) indicated that the nonmigrating tides play an important role in the nighttime ion upward drift.…”
Section: Influences Of Solar Terminator Waves On the Midnight Epb Dev...mentioning
confidence: 99%
“…Understanding the complexities of the underlying physics responsible for the day‐to‐day variability of EPBs remains a challenge. Various observation and modeling efforts have been conducted to investigate the underlying physics responsible for the day‐to‐day variability of EPBs, such as seed perturbations (Abdu et al., 2009; Krall et al., 2013; Retterer & Roddy, 2014; Singh et al., 1997), neutral winds (Huba & Krall, 2013; Huba et al., 2009; Krall et al., 2009, 2021; Maruyama & Matuura, 1984), vertical drifts (Retterer et al., 2005; Su et al., 2009), shear instability (Hysell & Kudeki, 2004; Yokoyama et al., 2015), Es‐layer instability (Huba et al., 2020; Tsunoda, 2007), tidal forcing (Chang et al., 2021; Chou, Wu, et al., 2020; Tsunoda et al., 2015), upwelling growth (e.g., Tsunoda, 2015), and penetration electric fields due to geomagnetic storms (e.g., Cherniak & Zakharenkova, 2016; Rajesh et al., 2017). These studies primarily focus on a single driver that controls EPB development, and artificial seed perturbations are required in the initial conditions for EPB simulations (e.g., Yokoyama, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies (e.g., Ajith et al., 2016; Dao et al., 2016, 2017; Krall et al., 2021; Sun, Xu, Zhu, Yuan, & Zhao, 2021; Yokoyama et al., 2011) found that equatorward neutral winds can also initialize freshly‐generated EPBs around midnight. Those studies suggest that the uplift of the ionosphere by equatorward neutral winds could lead to a decrease in the frequency of ion‐neutral collision, resulting in an increasing gravity‐driven eastward electric current that initializes EPBs above the geomagnetic equator by the RTI (Huba & Krall, 2013; Nishioka et al., 2012).…”
Section: Introductionmentioning
confidence: 99%